Intralesional oxytetracycline injection for treatment of lower eyelid festoons - Intan Ramli; Elza Iskandar; Theodorus Theodorus (Majalah Oftalmologi Indonesia, 2017)
Introduction : Festoons of the lower eyelids are excess of loose skin and lower orbicular muscles that hang from the cantal to the cantal. Some treatment options may improve the appearance of the festoons. Oxytetracycline has a function to block metalloproteinase matrix so that serve to form structural proteins and building tissues and improving collagen conditions for skin elasticity. Objective to determine the efficacy of oxytetracycline intralesional injection for treatment of lower eyelid festoons on patients in Palembang, South Sumatra. Method : Clinical Trial without comparison of patients undergoing oxytetracycline 2% injection of lower eyelidfestoons was conducted at RSMH Eye Clinic Palembang from November 2016 unÂ til March 2017. There were 32 samples of lower eyelid festoons on patients aged over 35 years old who met inclusion and exclusion criteria. Frequency and data sharing. Data is calcuÂ lated with AutoCAD program and analyzed using the Paired T Test and the Wilcoxon Test Results : Thirty two samples of lower eyelid festoons on patients aged ranges 41 to 69 years. Follow up was 4 weeks. Patients received 0,3cc of oxytetracyline 2% intralesion. There were a high differences of festoons at preinjection and 2 weeks after injections of 0.074cm (p=0,000) and preinjection at 4 weeks after injection of 0.142cm (p=0,000) There were a differences of festoons in length at preinjection and 2 weeks after injection of 0.053cm (p=0,000) and preinjection at 4 weeks after injection of 0.172cm (p=0,000). Conclusion : Intralesional oxytetracycline 2% injection was effective for treatment of lower eyelid festoons on patients in Palembang, South Sumatra.